Laser welding of AZ31Mg alloy with 6061Al alloy via Ti interlayer based on two kinds of bonding mechanisms. (November 2022) - Lv, Xinze; Liu, Liming; Song, Gang
Abstract: Fusion welding of Mg-Al dissimilar metals is of great challenge because the number of intermetallic compounds (IMCs) is hard to control. Generally speaking, the thickness of IMC layer is about tens of microns. In this paper, we proposed a novel method to control the brittle IMCs more effectively by designing a hybrid joint based on two different kinds of joining mechanisms. In the experiment, laser welding of AZ31 Mg alloy to 6061 Al alloy with Ti interlayer was performed. The laser power was precisely controlled to ensure that the Ti interlayer was not penetrated. In this case, the top Mg alloy and the surface of Ti interlayer were melted and fusion welding process was realized at the Mg/Ti interface. While the heat was conducted from the residual solid Ti interlayer to the bottom Al alloy base metal and brazing process was obtained at the Ti/Al interface. The reaction layers formed at Mg/Ti and Ti/Al interfaces are 100 nm thick Ti3 Al and 1.5 um thick TiAl3 IMCs, respectively. The joint fractured at the Mg fusion zone with the maximum fracture load of 1684 N/cm, which was 40 % higher than that of reported studies on Mg-Al laser welding (less than 1200 N/cm).